Enhancing collaborative online learning in higher education: using Google Docs to analyze Literature texts by teacher trainees - Nambi, Rebecca (East African Journal of Education Studies, 2024)
The purpose of this project was to explore how collaborative learning can be enhanced through Information Communications Technology in the critical reading and analysis of Literature texts in a particular teacher training course at a selected university in Uganda. The study undertook an interventional research approach whereby critical literacy principles provided the basis for formulating online tasks that would provoke higher order thinking skills such synthesizing, analyzing, reasoning, comprehending, application, and evaluation during the discussion of the play The Lion and the Jewel. A conversational framework was adopted to design a collaborative learning environment by which face-to-face sessions were combined with technology in form of Google Docs. Some of the steps of engagement included identifying the eight participants, sharing of initial content on critical literacy with them, face-to-face sessions and uploading of tasks. The findings reveal that with systematic instructions and guidance Google Docs can provide a collaborative learning platform whereby students can continuously comment about Literature texts in a conversational manner; the intervention proved the possibilities of flexibility in the learning environment; and dialogic teaching especially when discussing Literature texts was greatly enhanced during this intervention. This study was carried out in a real time learning context during the teaching of one of the researcher’s courses. The finding thus can offer some useful guiding steps as benchmarks for actual take up of other ICT tools in teaching and learning in higher institutions of education